U-X-L encyclopedia of weather and natural disasters - Hackney Blackwell, Amy; Manar, Elizabeth P.; Gale Group (Farmington Hills, Mich. U-X-L, a part of Gale Cengage Learning, 2016)
Introduces students to the topic of weather and natural disasters, covering such topics as weather basics, weather phenomena, forecasting, and climate. Provides information on the scientific aspects of various types of disasters including: blizzards, earthquakes, flooding, tornadoes, volcanoes, and wildfires.
volume 1. A-C -- volume 2. D-G -- volume 3. H-O -- volume 4. P-T -- volume 5. U-Z.
Includes bibliographical references and index.
Keywords: Meteorology -- Encyclopedias, Juvenile; Natural disasters -- Encyclopedias, Juvenile